Effect of Vestibular Rehabilitation on Kinetic and Kinematic Parameters of Gait in Patients With Multiple Sclerosis: A Single-Blind Randomized Controlled Study - Uzunoglu, Gamze Ertürk; Yeldan, Ipek; Celik, Rabia Gokcen Gozubatik; KUCHIMOV, SHAVKAT NADIR; Tütüncü, Mesude (Elsevier Sci Ltd., 2025)
Background: Multiple sclerosis (MS) patients frequently experience gait disturbances, which can be exacerbated in those with vestibular involvement. Various exercise approaches are available to address gait difficulties in this patient population, and the use of vestibular rehabilitation, in particular, has increased recently. However, the effects of this specific exercise approach on gait in MS patients remain unclear. Considering that gait comprises temporospatial, kinetic, and kinematic components, it is evident that existing research in this area is fairly limited. Therefore, our study aimed to evaluate the effect of a vestibular rehabilitation program compared to a conventional exercise program on kinetic and kinematic parameters of gait in patients with MS. Methods: MS patients aged 25-60 years with an EDSS score between 3.5 and 6.5 were included in the study. Participants were randomly assigned to either the vestibular rehabilitation group or the conventional exercise group. All participants underwent primary evaluation with Three-dimensional gait analysis and secondary assessments using the 2-Minute Walk Test, 10-Meter Walk Test, 5-Times Sit to Stand Test, and Visual Acuity Test. Results: The study was completed with 22 participants [age: 45.18 +/- 10.22, EDSS: 4.00 (3.50 - 5.00)]. Pelvic tilt range of motion, knee varus/valgus, ankle maximum external rotation, mean ankle rotation angles and the peak knee extension moment in the 30-60 % cycle of gait showed statistically greater improvement in the vestibular rehabilitation group compared to the conventional exercise group in post-treatment. After exercise trainings, there was no significant difference in temporospatial data between the two groups. Discussion: It was concluded that supporting the rehabilitation programs of MS patients with VR exercises contributed to the improvement of various kinetic and kinematic parameters of gait.
Keywords: Xercise; Gait Analysis; Multiple Sclerosis; Rehabilitation; Vestibular